Kaempferol Suppresses Proliferation and Induces Cell Cycle Arrest, Apoptosis, and DNA Damage in Breast Cancer Cells - Zhu, Li (Oncol Res, 2019)
Kaempferol is a flavonoid that has been extensively investigated owing to its antitumor effects. Nevertheless, little is known about its underlying mechanisms of action. We aimed to explore the role of kaempferol in breast cancer (BC), and thus we investigated how kaempferol suppresses the growth of BC cells. The cells were treated with kaempferol, and the effects on multiple cancer-associated pathways were evaluated. The MTS assay was used to study the cell growth inhibition induced by kaempferol. The cell cycle was analyzed by flow cytometry. Western blotting was used to analyze cellular apoptosis and DNA damage. We found that the proliferation of the triple-negative BC (TNBC) MDA-MB-231 cells was suppressed effectively by kaempferol. Interestingly, the suppressive effect of kaempferol on cell proliferation was stronger in MDA-MB-231 cells than in the estrogen receptor-positive BT474 cell line. Furthermore, after the treatment with kaempferol for 48 h, the population of cells in the G(1) phase was significantly reduced, from 85.48% to 51.35%, and the population of cells in the G(2) phase increased markedly from 9.27% to 37.5%, which indicated that kaempferol contributed to the induction of G(2)/M arrest. Kaempferol also induced apoptosis and DNA damage in MDA-MB-231 cells. Kaempferol increased the expression levels of γH2AX, cleaved caspase 9, cleaved caspase 3, and p-ATM compared to those of the control group. Collectively, these results showed that kaempferol may be a potential drug for the effective treatment of TNBC.